Manual de Responsabilidad Social Empresarial para la gestión de las empresas comerciales: caso “Empresa de Materiales de Construcción cia, ltda, Enrique Ullauri del Cantón catamayo” - Paz Abarca, Ronald Dario (2021)
Social responsibility has become an element for management, incorporating competitive advantages and intervening in a sustainable manner. It involves recognizing and integrating business activities, taking care of the economic, social, environmental and labor issues. Enrique Ullauri is a company that carries out activities of purchase, sale and distribution of construction materials, this company welcomes corporate social responsibility not as a fashion or a social imposition, but rather as a commitment in the construction of an improvement to society, through activities and actions that positively affect the company. In this degree work, focuses on a research to implement the practices of social responsibility with new management trends, with this purpose to present a manual of corporate social responsibility applicable to the company "Enrique Ullauri CIA Ltda.". It will be done with the purpose of developing an instrument that allows you to enter into an organizational culture to generate administrative efficiency, improve the relationship of its employees, customers and the parties that make up the organization. The objective of this study is to elaborate the corporate social responsibility manual through the ISO 26000 standard, in which each of the subjects of said standard were taken both for the elaboration of the surveys and for the elaboration of said manual. The research was aided by the review of different manuals that led to the development of the manual, the concepts of CSR were also reviewed, especially the ISO 26000 standard, which will be the main one for the development of this manual. In the methodology, the factors involved in the organization were identified in order to prioritize according to their influence. In the results we present the interpretation and analysis in which we take into account the surveys made to the clients and employees, evidencing the knowledge they have about the corporate social responsibility. This analysis will be based on the ISO 26000 standard that was the pillar for the elaboration of the questionnaire. Finally, each of the activities that the company should carry out in each of the subjects was determined, with this proposal it is sought to increase the development in a feasible way for the sector of study.